INNOVATIVE DEVELOPMENT OF THE PHARMACEUTICAL INDUSTRY - Sabohat Sobid qizi, Usmanova («YANGI O'ZBEKISTON IQTISODIYOTI», 2026)
The purpose of this study is to examine the innovative development of the pharmaceutical industry under the conditions of globalization and structural transformation of the economy. The research is based on a comparative and institutional analysis of industry development factors, as well as a qualitative assessment of state regulation and localization processes in the pharmaceutical sector of Uzbekistan. The paper substantiates the role of innovation clusters as an institutional mechanismfor enhancing competitiveness and ensuring sustainable growth of the industry. Particular attention is given to the integration of localization strategies, technology transfer, and research and development (R&D) activities in the formation of a value-added chain within the pharmaceutical sector. The results demonstrate that the development of cluster-based models and the implementation of international standards contribute to increasing innovation efficiency, reducing import dependence, and strengthening export potential. The findings may be applied in the formulation of industrial and innovation policy aimed at the modernization of the national pharmaceutical industry.